2005
DOI: 10.1124/jpet.105.092452
|View full text |Cite
|
Sign up to set email alerts
|

The δ Subunit of γ-Aminobutyric Acid Type A Receptors Does Not Confer Sensitivity to Low Concentrations of Ethanol

Abstract: GABA A receptors (GABA A Rs) are usually formed by ␣, ␤, and ␥ or ␦ subunits. Recently, ␦-containing GABA A Rs expressed in Xenopus oocytes were found to be sensitive to low concentrations of ethanol (1-3 mM). Our objective was to replicate and extend the study of the effect of ethanol on the function of ␣ 4 ␤ 3 ␦ GABA A Rs. We independently conducted three studies in two systems: rat and human GABA A Rs expressed in Xenopus oocytes, studied through two-electrode voltage clamp; and human GABA A Rs stably expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(179 citation statements)
references
References 40 publications
9
167
3
Order By: Relevance
“…Several neuroactive steroids (5α-pregnane-3α-ol-20-one, alphaxalone, and 5α-pregnane-3α,21-diol-20-one or THDOC) were more potent modulators of GABA in α 4 β 3 δ than in α 4 β 3 γ 2 GABA A -Rs. More recent studies of human and rat α 4 β 3 δ expressed in oocytes replicated many of these findings (Borghese et al, 2006;Stórustovu and Ebert, 2006).…”
Section: Expression In Heterologous Systemssupporting
confidence: 54%
See 1 more Smart Citation
“…Several neuroactive steroids (5α-pregnane-3α-ol-20-one, alphaxalone, and 5α-pregnane-3α,21-diol-20-one or THDOC) were more potent modulators of GABA in α 4 β 3 δ than in α 4 β 3 γ 2 GABA A -Rs. More recent studies of human and rat α 4 β 3 δ expressed in oocytes replicated many of these findings (Borghese et al, 2006;Stórustovu and Ebert, 2006).…”
Section: Expression In Heterologous Systemssupporting
confidence: 54%
“…Four labs tested ethanol sensitivity of α 4 -and δ-containing GABA A -Rs in different systems, and did not observe any sensitivity to low concentrations of ethanol (Borghese et al, 2006). Our laboratory's setting most closely resembled that used by Olsen's group, since we used the same rat cDNAs, and followed their protocols.…”
Section: Lack Of Sensitivity To Low Concentrations Of Ethanolmentioning
confidence: 99%
“…However, these statements deserve caution, given that the systems level approach of our experiments does not permit direct insights into the cellular mechanisms. Furthermore, the high sensitivity of extrasynaptic GABAARs to low doses of EtOH has not been unanimously replicated (Borghese et al, 2006;Yamashita et al, 2006).…”
Section: Drug Effects On Pas Ltp -Induced Ltp-like Increase Of Mep Iomentioning
confidence: 99%
“…Cellular studies showed that low-dose EtOH (p30 mM) produces mainly two effects: potentiation of extrasynaptic gamma-aminobutyric acid type A receptor (GABAAR)-mediated tonic inhibition (Sundstrom-Poromaa et al, 2002;Wallner et al, 2003;Wei et al, 2004) (for review, (Olsen et al, 2007)), although this has not been unanimously supported (Borghese et al, 2006;Yamashita et al, 2006), and N-methyl-D-aspartate receptor (NMDAR) inhibition (Lovinger et al, 1989(Lovinger et al, , 1990Weitlauf and Woodward, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these results generated some controversy in the field as the findings regarding the high alcohol affinity of the extra-synaptic receptors have not been replicated by some groups and presynaptic mechanisms have been proposed for the alcohol potentiation of GABAergic system (Carta et al, 2004;Borghese et al, 2006;Botta et al, 2007a, b;Korpi et al, 2007;Baur 2009). Several experimental errors or methodological issues may cause this contradiction.…”
Section: Alcohol and Extra-synaptic Gabaarsmentioning
confidence: 99%